How reliable are administrative reports of paid work hours? - Marta Lachowska; Alexandre Mas; Stephen A. Woodbury (W.E. Upjohn Institute for Employment Research, 2022)
This paper examines the quality of quarterly records on work hours collected from employers in the State of Washington to administer the unemployment insurance (UI) system, specifically to determine eligibility for UI. We subject the administrative records to four "trials," all of which suggest the records reliably measure paid hours of work. First, distributions of hours in the administrative records and Current Population Survey outgoing rotation groups (CPS) both suggest that 52-54% of workers work approximately 40 hours per week. Second, in the administrative records, quarter-to-quarter changes in the log of earnings are highly correlated with quarter-to-quarter changes in the log of paid hours. Third, annual changes in Washington's minimum wage rate (which is indexed) are clearly reflected in year-to-year changes in the distribution of paid hours in the administrative data. Fourth, Mincer-style wage rate and earnings regressions using the administrative data produce estimates similar to those found elsewhere in the literature.
Keywords: C81; H83; J65; 330; unemployment insurance; administrative data; paid work hours; data quality